2023
DOI: 10.1021/jacs.3c06144
|View full text |Cite
|
Sign up to set email alerts
|

3site Multisubstrate-Bound State of Cytochrome P450cam

Mohammad Sahil,
Tejender Singh,
Soumya Ghosh
et al.

Abstract: We identified a multisubstrate-bound state, hereby referred as a 3site state, in cytochrome P450cam via integrating molecular dynamics simulation with nuclear magnetic resonance (NMR) pseudocontact shift measurements. The 3site state is a result of simultaneous binding of three camphor molecules in three locations around P450cam: (a) in a well-established "catalytic" site near heme, (b) in a kink-separated "waiting" site along channel-1, and (c) in a previously reported "allosteric" site at E, F, G, and H heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“… 54 Here, we would like to note that the application of HMR might alter the time scales of the studied processes, as shown recently. 55 , 56 Hence, in studies aimed at measuring the absolute rates, unlike the primarily comparative work here, it might be advisable to avoid HMR.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“… 54 Here, we would like to note that the application of HMR might alter the time scales of the studied processes, as shown recently. 55 , 56 Hence, in studies aimed at measuring the absolute rates, unlike the primarily comparative work here, it might be advisable to avoid HMR.…”
Section: Methodsmentioning
confidence: 95%
“…Such a system was then processed with the tleap module of AMBERTools18, placing the presolvated proteins in the octahedral box of OPC water molecules at a distance of 10 Å and neutralizing them with counterions (Na + and Cl – ) at an ionic strength of 0.1 M. Finally, the hydrogen mass repartitioning (HMR) method was applied to produce topologies to enable a 4 fs time step . Here, we would like to note that the application of HMR might alter the time scales of the studied processes, as shown recently. , Hence, in studies aimed at measuring the absolute rates, unlike the primarily comparative work here, it might be advisable to avoid HMR.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the aforementioned mechanistic insights, the molecular mechanism of the P450-catalyzed biosynthesis of DKPs is not fully elucidated, especially regarding the protein environment effects in dictating the regio- and stereoselective C–N and C–C coupling. Extensive studies have shown that the protein environment is key to the activity and selectivity of enzyme catalysis, while the neglect of such an effect in the QM model calculations may give biased descriptions of the kinetic and thermodynamic properties of enzymatic processes. , In this study, we reexamined the molecular mechanism of the P450 NascB with the combined MD simulations , and quantum mechanical/molecular mechanical (QM/MM) calculations. Particularly, we systematically explored all conceivable catalytic pathways originating from two distinct binding modes of Substrate 1. Our multiscale calculations reveal that pathway B, which involves a conformational movement of the substrate radical, is the most favorable reaction pathway.…”
Section: Introductionmentioning
confidence: 99%